Goniometry and fleximetry measurements to assess cervical range of motion in individuals with chronic neck pain: a validity and reliability study - Gabriel Gardhel Costa Araujo; André Pontes-Silva; Plínio da Cunha Leal; Bruno Sousa Gomes; Maisa Lopes Reis; Sâmira Kennia de Mello Pereira Lima; Cid André Fidelis-de-Paula-Gomes; Almir Vieira Dibai-Filho (BMC Musculoskeletal Disorders, 2024)
Abstract Purpose To assess the test–retest and inter-rater reliability of goniometry and fleximetry in measuring cervical range of motion in individuals with chronic neck pain. Methods A reliability study. Thirty individuals with chronic neck pain were selected. Cervical range of motion was measured by goniometry and fleximetry at two time points 7 days apart. To characterize the sample, we used the numerical pain rating scale, Pain-Related Catastrophizing Thoughts Scale, and Neck Disability Index. Intraclass correlation coefficient (ICC), standard error of measurement (SEM) and minimum detectable change (MDC) were calculated. Correlations between goniometry and fleximetry measurements were performed using Spearman’s correlation coefficient (rho). Results For goniometry, we found excellent test–retest reliability (ICC ≥ 0.986, SEM ≤ 1.89%, MDC ≤ 5.23%) and inter-rater reliability (ICC ≥ 0.947, SEM ≤ 3.91%, MDC ≤ 10.84%). Similarly, we found excellent test–retest reliability (ICC ≥ 0.969, SEM ≤ 2.71%, MDC ≤ 7.52%) and inter-rater reliability (ICC ≥ 0.981, SEM ≤ 1.88%, MDC ≤ 5.20%) for fleximetry. Finally, we observed a strong correlation between the goniometry and the fleximetry for all cervical movements (rho ≥ 0.993). Conclusion Goniometry and fleximetry measurements are reliable for assessing cervical range of motion in individuals with chronic neck pain.